Tyre with radial carcass reinforcement

By using isoprene elastomer, pyrolyzed carbon black reinforced filler and crosslinking system in the tire rubber mixture, the problem of rolling resistance and stiffness decrease in the rubber mixture when improving oxygen impermeability and reactivity in the prior art is solved, and better performance and environmental protection effects are achieved.

CN119630541APending Publication Date: 2025-03-14MICHELIN & CO (CIE GEN DES ESTAB MICHELIN)
View PDF 33 Cites 0 Cited by

Patent Information

Application Number
CN202380056794.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While improving oxygen impermeability and reactivity with oxygen, existing tire rubber mixtures are difficult to maintain good rolling resistance and stiffness, and increase the risk of hysteresis and moldability.

Method used

A rubber mixture containing isoprene elastomer, a reinforcement filler of 40 phr to 70 phr (at least 10 phr of pyrolyzed carbon black) and a crosslinking system is used, and the mixture is used between the carcass reinforcement and the tire cavity.

Benefits of technology

The oxygen impermeability and reactivity of the rubber mixture is improved while maintaining good rolling resistance and stiffness, reducing hysteresis and moldability risks, and reducing environmental footprints through the use of recycled materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630541A_ABST
    Figure CN119630541A_ABST
Patent Text Reader

Abstract

The invention relates to a tire with a radial carcass reinforcement. The invention relates to a tyre comprising, between the reinforcing elements of the carcass reinforcement and the tyre cavity, a rubber mixture comprising a composition based on:-an isoprene elastomer; -from 40 phr to 70 phr of a reinforcing filler comprising at least 10 phr, preferably at least 30 phr, of pyrolytic carbon black; and-a crosslinking system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to tires with radial carcass reinforcement and more particularly to tires intended to be fitted to vehicles carrying heavy loads and travelling at sustained speeds, such as, for example, trucks, tractors, trailers and buses. Background Art

[0002] Typically, a tire comprises a tread intended to come into contact with the ground through its tread surface, the two axial ends of which are connected by two sidewalls to two beads providing a mechanical connection between the tire and the rim on which it is intended to be mounted. A radial tire also comprises a reinforcement constituted by a crown reinforcement radially on the inside of the tread and a carcass reinforcement radially on the inside of the crown reinforcement.

[0003] The rubber compound located between the carcass reinforcement and the tire cavity (more specifically between the carcass reinforcement and the tire airtight layer) must be a chemical barrier and a physical barrier to oxygen to limit the diffusion of oxygen into the tire. Therefore, the rubber compound must be able to react with oxygen (chemical barrier) and be impermeable to oxygen (physical barrier).

[0004] This rubber compound contributes to the durability of the tire by limiting the diffusion of oxygen in the underlying area of ​​the tire and / or in the crown.

[0005] It is known to those skilled in the art that the reactivity of rubber mixtures with oxygen can be increased by increasing the sulfur content in the mixture. However, this increase in reactivity with oxygen is accompanied by a greater risk of forming nodes during the molding of the mixture due to a decrease in the curing t0 of the mixture.

[0006] It is also known to those skilled in the art that the air impermeability (and therefore oxygen impermeability) of a rubber mixture can be increased by increasing the content of reinforcing fillers (e.g. carbon black) in the mixture. However, such an increase in impermeability can impair the rolling resistance of the tire, and an increase in the content of reinforcing fillers can also increase hysteresis.

[0007] Therefore, there is still a need to provide a rubber mixture that can be placed between the carcass reinforcement and the tire cavity, more specifically between the carcass reinforcement and the airtight layer of the tire, with improved oxygen impermeability and reactivity with oxygen and better rolling resistance, while having a maintained level of stiffness and without affecting the moldability of the mixture. Advantageously, the proposed solution can reduce the environmental footprint of tires with radial carcass reinforcements by introducing a significant portion of recycled materials. Summary of the invention

[0008] The present invention relates to a tire having a radial carcass reinforcement consisting of at least one layer of reinforcing elements, comprising a crown reinforcement which is itself radially covered by a tread connected to two beads by two sidewalls, characterized in that the tire comprises, between the reinforcing elements of the carcass reinforcement and the tire cavity, a rubber mixture comprising a composition based on:

[0009] - isoprene elastomer;

[0010] - 40 to 70 phr of reinforcing filler, said reinforcing filler comprising at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black; and

[0011] - Cross-linking system.

[0012] Other aspects of the invention are described below and in the claims.

[0013] definition

[0014] The expression "composition based on" is understood to mean that the composition comprises a mixture and / or in situ reaction products of the various components used, some of which are able and / or intended to react at least partially with one another during the various manufacturing stages of the composition; the composition may therefore be in a completely crosslinked or partially crosslinked state or in a non-crosslinked state.

[0015] The expression “parts by weight per hundred parts by weight of elastomer” (or phr) is understood to mean parts by mass per hundred parts by mass of elastomer or rubber (the two terms being synonymous).

[0016] In the present application, unless otherwise expressly stated, all percentages (%) shown are mass percentages (%).

[0017] In addition, any numerical interval represented by the expression "between a and b" means a numerical range extending from greater than a to less than b (i.e., excluding the limits a and b), while any numerical interval represented by the expression "a to b" means a numerical range extending from a to b (i.e., including the strict limits a and b). In the present application, when a numerical interval is described by the expression "a to b", it is preferred to also describe the interval represented by the expression "between a and b".

[0018] The expression "radial" refers to the radius of the tire. Within this meaning, a point P1 is said to be located "radially inside" a point P2 (or "radially on the inside of point P2") if it is closer to the axis of rotation of the tire than point P2. Conversely, a point P3 is said to be located "radially outside" a point P4 (or "radially on the outside of point P4") if it is further away from the axis of rotation of the tire than point P4. When proceeding in the direction of a smaller (or larger) radius, one is said to proceed "radially inwards (or outwards)". This meaning of the terms also applies when radial distances are concerned.

[0019] Here, the term "radial cross section" or "radial section" is understood to mean a cross section or section along a plane that includes the axis of rotation of the tyre.

[0020] The "axial" direction is the direction parallel to the axis of rotation of the tire. Point P5 is said to be "axially inside" (or "axially inside") point P6 if point P5 is closer to the median plane of the tire than point P6. Conversely, point P7 is said to be "axially outside" (or "axially outside" of point P8) if point P7 is further from the median plane of the tire than point P8. The "median plane" of the tire is the plane perpendicular to the axis of rotation of the tire and equidistant from the annular reinforcing structure of each bead.

[0021] A "circumferential" direction is a direction perpendicular to the radius and axial directions of the tire.

[0022] The carbon-containing compounds mentioned in the specification can be compounds of fossil origin or bio-based origin. In the case of compounds of bio-based origin, they can be partially or completely derived from biomass, or obtained by renewable raw materials derived from biomass. This particularly relates to polymers, plasticizers, fillers, etc.

[0023] The curing t0 of a rubber mixture denotes the time during which the mixture can be processed before crosslinking bridges are formed (induction time).

[0024] Detailed description of the invention

[0025] Surprisingly, the inventors have found that the use of pyrolytic carbon black in rubber mixtures makes it possible to improve the reactivity of said mixtures with oxygen and the oxygen impermeability without reducing the level of stiffness, while reducing the level of hysteresis and increasing the cure t0 of the mixture.

[0026] The present invention therefore relates to a tire having a radial carcass reinforcement consisting of at least one layer of reinforcing elements, said tire comprising a crown reinforcement which is itself radially covered by a tread connected to two beads by two sidewalls, characterized in that said tire comprises, between the reinforcing elements of the carcass reinforcement and the tire cavity, a rubber mixture comprising or consisting of a composition based on:

[0027] - isoprene elastomer;

[0028] - 40 to 70 phr of reinforcing filler, said reinforcing filler comprising at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black; and

[0029] - Cross-linking system.

[0030] The compositions may also contain customary additives and processing aids.

[0031] The various components of the composition may be as described below.

[0032] Elastomer

[0033] The composition used in the context of the present invention is based on isoprene elastomer.

[0034] The term “isoprene elastomer” is understood in a known manner to mean an isoprene homopolymer or copolymer, in other words an elastomer chosen from natural rubber (NR), synthetic polyisoprenes (IR), isoprene copolymers (for example copolymers of isobutylene and isoprene) and mixtures thereof.

[0035] Preferably, the composition used in the context of the present invention is based on an isoprene elastomer chosen from natural rubber, synthetic polyisoprene and mixtures thereof. Thus, the elastomer is generally composed of 70 to 100 phr of natural rubber and 0 to 30 phr of synthetic polyisoprene.

[0036] In certain embodiments, the composition used in the context of the present invention is based on natural rubber. In other words, the composition does not contain any other elastomer.

[0037] Reinforcement filler

[0038] The composition used in the context of the present invention comprises from 40 to 70 phr of reinforcing filler, including at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black.

[0039] The term “reinforcing filler” means any type of filler known to be capable of reinforcing rubber compositions that can be used in particular for making tires, such as organic fillers, such as carbon black or pyrolytic black, or inorganic fillers, such as silica or alumina.

[0040] Thus, the composition may comprise, in addition to the pyrolytic carbon black, an inorganic reinforcing filler, such as silica or alumina, or an organic reinforcing filler, such as carbon black, to achieve a total content of reinforcing filler ranging from 40 to 70 phr.

[0041] In certain embodiments, the composition comprises 40 to 70 phr of a reinforcing filler, which is pyrolytic carbon black. Therefore, it should be understood that the composition comprises pyrolytic carbon black as the only reinforcing filler (therefore, the composition does not comprise any inorganic reinforcing filler and other organic reinforcing fillers).

[0042] The reinforcing filler may be as described below.

[0043] Pyrolytic Carbon Black

[0044] The composition used in the context of the present invention comprises at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black.

[0045] In certain embodiments, the composition comprises 40 phr to 70 phr of pyrolytic carbon black.

[0046] For the purposes of the present invention, the term "pyrolytic carbon black" is understood to mean carbon black resulting from a pyrolysis process of a material comprising at least a carbon-based polymer and carbon black (hereinafter referred to as material to be pyrolyzed), for example in the case of recycling such material. The physical state of the material to be pyrolyzed as provided is not important, whether it is in the form of a powder, granules, strips or any other form, in a crosslinked or non-crosslinked state.

[0047] Preferably, the material to be pyrolyzed can be recovered from a finished product or a product (e.g. a by-product or waste) generated during its manufacture / production; these finished products can be selected from pneumatic tires, non-pneumatic tires, industrial conveyor belts, conveyor belts, rubber seals, rubber hoses, shoe soles and windshield wipers. Still more preferably, the pyrolytic carbon black used in the context of the present invention is a carbon black obtained by a pyrolysis process of a material to be pyrolyzed originating from a finished product selected from pneumatic tires and non-pneumatic tires.

[0048] In the context of the present invention, "pyrolysis" means any type of thermal decomposition carried out in the absence of oxygen and the raw material thereof is the material to be pyrolyzed as defined above. Thus, pyrolytic carbon black differs from "industrial" carbon black and / or "ASTM grade" carbon black in that the carbon-based raw material used for pyrolysis is a material comprising at least a carbon-based polymer and carbon black, rather than a material derived from petroleum fractions or from coal or oils of natural origin.

[0049] The pyrolytic carbon blacks which can be used in the context of the present invention differ from the carbon blacks known as industrial carbon blacks, in particular “furnace” carbon blacks, in particular by having a higher ash content.

[0050] Preferably, the ash content of the pyrolytic carbon black useful in the present invention is in the range of 5 wt % to 30 wt %, more preferably in the range of 8 wt % to 25 wt %, even more preferably in the range of 10 wt % to 22 wt %, relative to the total weight of the pyrolytic carbon black.

[0051] Preferably, the sulfur content of the pyrolytic carbon black that can be used in the context of the present invention is greater than 2% by weight, preferably ranging from 2.5% to 5% by weight, relative to the total weight of the pyrolytic carbon black.

[0052] Preferably, the zinc content of the pyrolytic carbon black that can be used in the context of the present invention is greater than or equal to 2% by weight, preferably ranging from 2.5% to 8% by weight, relative to the total weight of the pyrolytic carbon black.

[0053] Preferably, the pyrolytic carbon black that can be used in the present invention has a STSA specific surface area of ​​20 m2 measured according to standard ASTM D6556-2021. 2 / g to 200m 2 / g, more preferably 30m 2 / g to 90m 2 / g range.

[0054] Preferably, the pyrolytic carbon black that can be used in the present invention has a void volume measured at a pressure of 50 MPa according to standard ASTM D7854 (2018) in the range of 30 ml / 100 g to 60 ml / 100 g, more preferably 35 ml / 100 g to 55 ml / 100 g.

[0055] The ash content is determined by calcination in a platinum dish in a muffle furnace at 825°C according to the following scheme. Before each series of measurements, the platinum dish is pre-determined and the tare weight of the platinum dish is weighed to an error of less than 0.1 mg, and the mass is denoted as P0. 5 g of the pyrolytic carbon black sample is introduced into the platinum dish and accurately weighed to an error of less than 0.1 mg; this mass is denoted as P1. The platinum dish and its contents are pre-calcined using a Bunsen burner until smoke appears and the product is ignited. After the combustion of the product is complete, the platinum dish and its contents are placed in a muffle furnace heated to 825°C for 1 h. After 1 h, the platinum dish is removed from the furnace and immediately placed in a desiccator at ambient temperature. When the platinum dish and the ash have returned to ambient temperature, the platinum dish is weighed again to obtain the mass P2. Finally, the ash content (% ash) can be obtained using the following formula:

[0056]

[0057] After the sample is calcined, the ash is absorbed in an acidic medium and then detected by ICP-AES (inductively coupled plasma atomic emission spectrometry) to determine the content of zinc in pyrolytic carbon black. The ash is obtained by carrying out the above scheme. About 100 mg of ash (sample) is taken and introduced into a PFA (perfluoroalkoxy) tube for a HotBIock hot plate. Then 8 ml of 37% concentrated hydrochloric acid, 3 ml of 65% concentrated nitric acid and 0.5 ml of 40% hydrofluoric acid are added. The tube is closed with a pipe stopper and heated to 130 ° C for 2 hours. After cooling, the contents are then transferred to a 100 ml PTFE (polytetrafluoroethylene) volumetric flask containing 2 g of boric acid (for neutralizing hydrofluoric acid) using ultrapure water. Ultrapure water is added until the scale line. The obtained solution was diluted 100 times by taking 1 ml of the solution and placing it in a 100 ml PFTE volumetric flask already containing 8 ml of 37% concentrated hydrochloric acid, 3 ml of 65% concentrated nitric acid, 0.5 ml of 40% hydrofluoric acid and 2 g of boric acid. The diluted solution was then filtered on a 0.45 μm GHP syringe filter before analysis by inductively coupled plasma atomic emission spectrometry (ICP-AES). Before analyzing the diluted solution, at least 5 standards with zinc concentrations of 0 mg / l, 0.5 mg / l, 1 mg / l, 2 mg / l and 5 mg / l were analyzed by ICP-AES. These standards were prepared by diluting a commercial solution with a certified zinc concentration of 1 g / l in a 100 ml volumetric flask.

[0058] These volumetric flasks already contain 8 ml of 37% concentrated hydrochloric acid, 3 ml of 65% concentrated nitric acid, 0.5 ml of 40% hydrofluoric acid and 2 g of boric acid. The standard solution is analyzed by ICP-AES at a wavelength of λZn=202.613 nm. For each standard concentration (c), the intensity IZn of the zinc signal is plotted on the curve IZn=f(c), which corresponds to the calibration straight line (y=ax+b type). Then, the sample solution (diluted solution) of unknown concentration is measured under the same conditions as the standard. The measured intensity is related to the concentration using the previously obtained calibration straight line. Since the sample and volume have been recorded in advance, the ash concentration [c] (in mass %) is directly obtained by the software. The concentration of zinc in pyrolytic carbon black [c] carbon black (in mass %) is obtained by the following equation:

[0059] [c] 炭黑 =[c] 灰分 *100*% ash

[0060] The sulfur content in pyrolytic carbon black is determined using a LECO furnace. The LECO sulfur analyzer is designed to measure the sulfur content in organic and / or inorganic materials, particularly by combustion and non-spectral infrared detection. Before measuring the sulfur content in the sample, clean the boat and calibrate the furnace. Pre-clean the boat for the LECO furnace: This involves analyzing an empty boat under the same conditions as the sample. A commercial standard called "BBOT" is used to draw a calibration curve, which has a purity greater than 99.99% and a guaranteed content of carbon (C), hydrogen (H), nitrogen (N), oxygen (O) and sulfur (S). The content is as follows: C%: 72.52; H% 6.09; N% 6.51; O% 7.43 and S% 7.44. About 10±3 mg, 20±3 mg and 40±3 mg of BBOT are weighed on the boat. The standard / boat assembly is introduced into the combustion furnace and adjusted to 1350°C under pure oxygen. The combination of the furnace temperature and the analysis flow rate causes the sample to burn and releases sulfur and / or carbon in the form of SO2(g). After a period of 20 seconds, oxygen begins to flow through the spray gun, thereby accelerating the combustion of difficult-to-burn materials. Sulfur and / or carbon in the form of SO2(g) are entrained by the oxygen flow through the infrared detection unit. The instrument software draws a straight line that relates the mass of the introduced standard sample to the response (area) observed on the detector. A calibration straight line is thus obtained. After carefully cleaning the sampling equipment, weigh approximately 80±5 mg of pyrolytic carbon black and introduce it into a boat for the LECO furnace. Use the calibration straight line to relate the area of ​​the observed SO2 peak to the concentration. Using the mass of the sample introduced into the boat, the instrument software then calculates the mass % of sulfur in the sample.

[0061] Pyrolytic carbon black is sold, for example, by BlackBear under the reference "BBCT30" or by Scandinavian EnviroSystems under the reference "P550".

[0062] Carbon Black

[0063] The composition used in the context of the present invention may contain carbon black.

[0064] Suitable carbon blacks are all carbon blacks, in particular the carbon blacks customarily used in tires or their treads, in particular industrial carbon blacks, more particularly “furnace” blacks.

[0065] Among the carbon blacks, mention will be made more particularly of the reinforcing carbon blacks of the 100, 200 and 300 series, or of the carbon blacks of the 500, 600 or 700 series (ASTM D-1765-2017 grades), such as for example N115, N134, N234, N326, N330, N339, N347, N375, N550, N683 and N772 carbon blacks. Preferably, the carbon black is selected from the carbon blacks of the 300, 500, 600 and 700 series.

[0066] Carbon black can be used in the commercially available single state, or in any other form (for example as a carrier for some rubber additives used). Carbon black may, for example, have been introduced into a diene elastomer (in particular an isoprene elastomer) in the form of a masterbatch (see, for example, applications WO 97 / 36724-A2 or WO 99 / 16600-A1).

[0067] Reinforced inorganic fillers

[0068] The compositions used in the context of the present invention may contain reinforcing inorganic fillers.

[0069] Here, the term "reinforcing inorganic filler" is understood to mean any inorganic or mineral filler, whatever its color and its origin (natural or synthetic), also called "white" filler, "transparent" filler or even "non-black" filler relative to carbon black, capable of reinforcing the rubber composition intended for the manufacture of tires alone, without requiring any means other than intermediate coupling agents. In a known manner, certain reinforcing inorganic fillers may be characterized in particular by the presence of hydroxyl (-OH) groups on their surface.

[0070] Mineral fillers of the siliceous type, preferably silicon dioxide (SiO2), or mineral fillers of the aluminous type, in particular aluminum oxide (Al2O3), are particularly suitable as reinforcing inorganic fillers. The silicon dioxide used may be any reinforcing silicon dioxide known to those skilled in the art, in particular, one having a BET specific surface area and a CTAB specific surface area of ​​less than 450 m 2 / g, preferably at 30m 2 / g to 400m 2 / g, especially 60m 2 / g to 300m 2 Any precipitated silica or fumed silica in the range of 100 Å / g.

[0071] Any type of precipitated silica may be used, in particular highly dispersible precipitated silica (HDS, for "highly dispersible silica"). These precipitated silicas, which may or may not be highly dispersible, are known to the person skilled in the art. For example, mention may be made of the silicas described in applications WO 03 / 016215-A1 and WO 03 / 016387-A1. Among the commercial HDS silicas, use may be made in particular of the silicas from Evonik. 5000GR and 7000GR silica, or from Solvay 1085GR, 1115MP, 1165MP, Premium200MP and HRS1200MP silica. As non-HDS silica, the following commercial silicas can be used: VN2GR and VN3GR Silica from Solvay 175GR silica, or Hi-Sil EZ120G(-D), Hi-Sil EZ160G(-D), Hi-Sil EZ200G(-D), Hi-Sil 243LD, Hi-Sil 210 and Hi-Sil HDP 320G silica from PPG.

[0072] The BET specific surface area of ​​the silica is determined in a known manner by gas adsorption using the Brunauer-Emmett-Teller method described in "The Journal of the American Chemical Society" (Vol. 60, p. 309, February 1938), more specifically in accordance with the French standard NF ISO 9277 of December 1996 (multipoint (5-point) volumetric method - gas: nitrogen - degassing: 1 hour at 160° C. - relative pressure p / po range: 0.05 to 0.17). The CTAB specific surface area of ​​the silica is determined in accordance with the French standard NF T 45-007 of November 1987 (method B).

[0073] As other examples of inorganic fillers that can be used in the composition, mention may also be made of mineral fillers of the aluminous type, in particular aluminium oxide (Al2O3), aluminium oxides, aluminium hydroxides, aluminium silicates, titanium oxides, silicon carbides or silicon nitrides, all reinforcing types as described for example in applications WO 99 / 28376-A2, WO 00 / 73372-A1, WO 02 / 053634-A1, WO 2004 / 003067-A1, WO 2004 / 056915-A2, US6610261-B1 and US6747087-B2. Mention may be made in particular of the aluminium oxides Baikalox A125 or CR125 APA-100RDX (Condéa), Aluminoxid C (Evonik), or AKP-G015 (Sumitomo Chemicals).

[0074] It is not important in what physical state the reinforcing inorganic filler is provided, whether it is in the form of a powder, microspheres, granules or beads or any other suitable densified form. Of course, the term "reinforcing inorganic filler" is also understood to mean mixtures of different reinforcing inorganic fillers, in particular mixtures of silica as described above.

[0075] A person skilled in the art will understand that it is possible to use a reinforcing filler of another nature as an alternative to the reinforcing inorganic fillers mentioned above, provided that the reinforcing filler of another nature is covered with an inorganic layer (for example silica) or comprises on its surface functional sites (in particular hydroxyl sites) requiring the use of a coupling agent to establish a bond between the reinforcing filler and the diene elastomer. Mention may be made, by way of example, of carbon blacks partially or completely covered with silica, or of carbon blacks modified with silica, such as, but not limited to, those of the CRX2000 series or the CRX4000 series from Cabot Corporation. Type filler.

[0076] The person skilled in the art knows how to adjust the total content of reinforcing filler according to the use involved, in particular according to the type of tire involved, for example tires for motorcycles, passenger vehicles or utility vehicles such as vans or heavy vehicles.

[0077] In order to couple the reinforcing inorganic filler to the diene elastomer, use may be made in a known manner of at least bifunctional coupling agents (or binders) intended to provide a connection of satisfactory chemical and / or physical nature between the inorganic filler (the surface of its particles) and the diene elastomer. Use is made in particular of at least bifunctional organosilanes or polyorganosiloxanes. The term "bifunctional" is understood to mean a compound having a first functional group capable of interacting with the inorganic filler and a second functional group capable of interacting with the diene elastomer. For example, such a bifunctional compound may comprise a first functional group containing a silicon atom, the first functional group being capable of interacting with the hydroxyl groups of the inorganic filler, and a second functional group containing a sulfur atom, the second functional group being capable of interacting with the diene elastomer.

[0078] Preferably, the organosilane is chosen from (symmetrical or asymmetrical) organosilane polysulfides, (such as bis(3-triethoxysilylpropyl)tetrasulfide (abbreviated to TESPT) sold under the name Si69 by Evonik, or bis(triethoxysilylpropyl)disulfide (abbreviated to TESPD) sold under the name Si75 by Evonik), polyorganosiloxanes, mercaptosilanes, blocked mercaptosilanes (such as S-(3-(triethoxysilyl)propyl)octanethioate sold under the name NXT Silane by Momentive). More preferably, the organosilane is an organosilane polysulfide.

[0079] Those skilled in the art can find examples of coupling agents in WO 02 / 083782, WO 02 / 30939, WO 02 / 31041, WO 2007 / 061550, WO 2006 / 125532, WO 2006 / 125533, WO 2006 / 125534, US 6849754, WO 99 / 09036, WO 2006 / 023815, WO 2007 / 098080, WO 2010 / 072685 and WO 2008 / 055986.

[0080] The content of coupling agent is preferably 0.5% to 15% by weight relative to the amount of reinforcing inorganic filler, preferably 4% to 12% by weight relative to the amount of reinforcing inorganic filler, more preferably 6% to 10% by weight. Usually, the content of coupling agent is less than 20phr, preferably in the range of 6phr to 17phr, preferably 8phr to 15phr. Those skilled in the art can easily adjust the content according to the content of inorganic filler used in the composition.

[0081] In addition to the coupling agents, the composition may also contain coupling activators, agents for coating the inorganic fillers or more generally processing aids which are able to improve the ease of processing of the composition in the unprocessed state in a known manner by improving the dispersion of the filler in the rubber matrix and reducing the viscosity of the composition, such as, for example, hydrolyzable silanes, for example alkylalkoxysilanes, in particular alkyltriethoxysilanes, polyols, polyethers, for example polyethylene glycols, primary, secondary or tertiary amines, for example trialkanolamines, hydroxylated or hydrolyzable POS, for example α,ω-dihydroxypolyorganosiloxanes, in particular α,ω-dihydroxypolydimethylsiloxanes, or fatty acids, such as, for example, stearic acid.

[0082] Other organic fillers

[0083] The composition used in the context of the present invention may comprise reinforcing organic fillers of the functionalized polyethylene type as described in applications WO 2006 / 069792-A1, WO 2006 / 069793-A1, WO 2008 / 003434-A1 and WO 2008 / 003435-A1.

[0084] Cross-linking system

[0085] The composition used in the context of the present invention comprises a crosslinking system.

[0086] The crosslinking system may be any type of system known to a person skilled in the art in the field of tire rubber compositions. The crosslinking system may in particular be based on sulfur and / or peroxides and / or bismaleimides.

[0087] Preferably, the crosslinking system is based on sulfur; it is then called a vulcanization system. The sulfur can be provided in any form, in particular in the form of molecular sulfur or a sulfur donor. It is also preferred that at least one vulcanization accelerator is present, and optionally, it is also preferred that various known vulcanization activators or known vulcanization retarders can be used, such as zinc oxide, stearic acid or equivalent compounds (e.g. stearates) and transition metal salts, guanidine derivatives (in particular diphenylguanidine).

[0088] Sulfur is used in preferred contents of between 0.5 and 12 phr, in particular between 1 and 10 phr, preferably between 2 and 9 phr.

[0089] Vulcanization accelerators are used in preferred contents between 0.1 and 10 phr, more preferably between 0.3 and 1.0 phr.

[0090] Vulcanization activators are used in preferred contents between 1 and 10 phr, more preferably between 3.3 and 10 phr.

[0091] As accelerator, use may be made of any compound capable of acting as an accelerator for the vulcanization of diene elastomers in the presence of sulfur, in particular accelerators of the thiazole type and derivatives thereof, or accelerators of the sulfenamide, thiuram, dithiocarbamate, dithiophosphate, thiourea and xanthate type. Mention may be made, as examples of such accelerators, of the following compounds: 2-mercaptobenzothiazole disulfide (abbreviated to "MBTS"), N-cyclohexyl-2-benzothiazole sulfenamide ("CBS"), N,N-dicyclohexyl-2-benzothiazole sulfenamide ("DCBS"), N-(tert-butyl)-2-benzothiazole sulfenamide ("TBBS"), N-(tert-butyl)-2-benzothiazole sulfenimide ("TBSI"), tetrabenzylthiuram disulfide ("TBZTD"), zinc dibenzyldithiocarbamate ("ZBEC") and mixtures of these compounds.

[0092] Commonly used additives and processing aids

[0093] The composition used in the context of the present invention may also contain all or part of the usual additives and processing aids known to the person skilled in the art and usually used in tire rubber compositions, such as, for example, plasticizers (e.g. plasticizing oils and / or plasticizing resins), non-reinforcing fillers, pigments, primary adhesion promoters (i.e. tackifiers, such as rosin), pro-oxidant metal salts, protective agents (e.g. anti-ozonant waxes, chemical antiozonants, antioxidants), anti-fatigue agents, reinforcing resins (as described, for example, in application WO 02 / 10269).

[0094] In certain embodiments, the compositions used in the context of the present invention comprise from greater than 0 phr to 5 phr of a primary adhesion promoter, such as from 1 phr to 5 phr of a primary adhesion promoter.

[0095] In certain embodiments, the composition used in the context of the present invention comprises from 0.3% to 4% by mass, preferably from 0.5% to less than 0.7% by mass, of one or more antioxidants relative to the total mass of the composition.

[0096] The antioxidant may be of the following type: amines, phenols, imidazoles, p-phenylenediamine and / or dihydrotrimethylquinoline, polymeric quinine, waxes or any other antioxidant commonly used in elastomer formulations.

[0097] As specific examples, mention may be made of: N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6-PPD, sold for example by Sumitomo Chemical Co., Ltd. under the trademark 6C and is trademarked by Ouchi Shinko Chemical Industrial Co., Ltd. 6C sold by Seiko Chemical Co., Ltd.; polymeric 1,2-dihydro-2,2,4-trimethylquinoline (TMQ, sold, for example, by RT Vanderbilt under the trademark Agerite Resin D); butylated hydroxytoluene (BHT); and butylated hydroxyanisole (BHA).

[0098] The antioxidant is advantageously an N-alkyl-N'-phenyl-p-phenylenediamine corresponding to formula (I):

[0099]

[0100] Where R 1 represents a linear or branched alkyl group having 1 to 12 carbon atoms or a cycloalkyl group having 5 to 8 carbon atoms.

[0101] Preferably, R 1 It represents an alkyl group having 2 to 8 carbon atoms (preferably selected from ethyl, propyl (i.e., n-propyl, isopropyl), butyl (i.e., n-butyl, sec-butyl and tert-butyl), pentyl, hexyl, heptyl and octyl) or a cycloalkyl group having 5 to 8 carbon atoms (cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl), more preferably cyclohexyl.

[0102] More preferably, the compound of the following formula (Ia) is used (wherein R 1 The group is branched):

[0103]

[0104] Where R 4 , R 5 are the same as or different from each other and each represents an alkyl group having the same carbon number as that specified above for R 1 Preferred definitions are given.

[0105] As a branched R 1 As more preferred examples of the group, mention will be made in particular of isopropyl, 1,3-dimethylbutyl and 1,4-dimethylpentyl.

[0106] The compounds of formula (Ia) above are well known to those skilled in the art. They have long been used as anti-aging protective agents in tire rubber compositions, in particular in the belt layers of these tires, and belong to the family of para-phenylenediamine ("PPD") derivatives, such as, for example, N-isopropyl-N'-phenyl-p-phenylenediamine ("I-PPD")

[0107]

[0108] or N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine ("6-PPD")

[0109]

[0110] (See for example applications WO 2004 / 033548, WO 2005 / 063510, WO 2005 / 133666).

[0111] In certain embodiments, the composition used in the context of the present invention comprises one or more pro-oxidant metal salts, the content of which varies from 0.05 g of metal to 0.15 g of metal per 100 g of the composition or from 0.07 g of metal to 0.15 g of metal per 100 g of the composition, determined based on the metal element.

[0112] Co-oxidant metal salts promote oxygen fixation by catalyzing oxidation.

[0113] These salts are well known to the person skilled in the art. Examples of metal salts of pro-oxidants include, in a non-limiting manner, cobalt salts (especially cobalt salts selected from abietic acid salts, acetylacetonates, fatty acid salts, naphthenates, resinates and mixtures thereof), manganese salts or iron salts (e.g., iron (III) salts as described in WO 99 / 24502 ​​or WO 00 / 68309).

[0114] In certain embodiments, the composition used in the context of the present invention is a composition based on:

[0115] - isoprene elastomer;

[0116] - 40 to 70 phr of reinforcing filler, said reinforcing filler comprising at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black;

[0117] - a cross-linking system, preferably the cross-linking system (eg a vulcanization system) comprises:

[0118] - between 0.5 and 12 phr, in particular between 1 and 10 phr, preferably between 2 and 9 phr of sulfur;

[0119] - between 0.1 phr and 10 phr, preferably between 0.3 phr and 1.0 phr, of one or more vulcanization accelerators;

[0120] - between 1 phr and 10 phr, preferably between 3.3 phr and 10 phr, of one or more vulcanization accelerators;

[0121] - 0.3% to 4% by mass, preferably 0.5% to less than 0.7% by mass, relative to the total mass of the composition, of one or more antioxidants; and

[0122] - one or more pro-oxidant metal salts, the content of which varies from 0.05 g to 0.15 g of metal per 100 g of composition, preferably from 0.07 g to 0.15 g of metal per 100 g of composition, determined on the basis of the metal element.

[0123] Specific Implementation

[0124] In certain embodiments, the composition used in the context of the present invention is a composition based on:

[0125] - isoprene elastomer;

[0126] - 40 to 70 phr of reinforcing filler, said reinforcing filler comprising at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black;

[0127] - a cross-linking system, preferably the cross-linking system (eg a vulcanization system) comprises:

[0128] - between 0.5 and 12 phr, in particular between 1 and 10 phr, preferably between 2 and 9 phr of sulfur;

[0129] - between 0.1 phr and 10 phr, preferably between 0.3 phr and 1.0 phr, of one or more vulcanization accelerators;

[0130] - between 1 phr and 10 phr, preferably between 3.3 phr and 10 phr, of one or more vulcanization activators; and

[0131] - 0.7% to 4% by mass, preferably 0.8% to 4% by mass, of one or more antioxidants relative to the total mass of the composition.

[0132] The composition may also contain one or more pro-oxidant metal salts, the content of which varies, determined on the basis of the metal, from 0.05 to 0.15 g of metal per 100 g of the composition, preferably from 0.07 to 0.15 g of metal per 100 g of the composition.

[0133] The inventors have found that the use of pyrolytic carbon black in rubber mixtures advantageously makes it possible to increase the antioxidant content of said mixtures without reducing the ability of the mixture to react with oxygen and without reducing the curing t0 of the mixture.

[0134] In certain embodiments, the composition used in the context of the present invention is a composition based on:

[0135] - isoprene elastomer;

[0136] - 40 to 70 phr of reinforcing filler, said reinforcing filler comprising at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black;

[0137] - a cross-linking system, preferably the cross-linking system (eg a vulcanization system) comprises:

[0138] - between 0.5 and 12 phr, in particular between 1 and 10 phr, preferably between 2 and 9 phr of sulfur;

[0139] - between 0.1 phr and 10 phr, preferably between 0.3 phr and 1.0 phr, of one or more vulcanization accelerators;

[0140] - between 1 phr and 10 phr, preferably between 3.3 phr and 10 phr, of one or more vulcanization activators; and

[0141] - Less than 0.07 g of metal derived from the self-oxidant metal salt per 100 g of the composition, preferably less than 0.05 g, or even less than 0.02 g or less than 0.01 g of metal derived from the self-oxidant metal salt per 100 g of the composition, even more preferably 0 g of metal derived from the self-oxidant metal salt.

[0142] The composition also comprises from 0.3% to 4% by mass, preferably from 0.5% to less than 0.7% by mass, of one or more antioxidants relative to the total mass of the composition.

[0143] The inventor has found that using pyrolytic carbon black in rubber mixtures can advantageously reduce the content of metal salts, without reducing the reactivity with oxygen, while increasing the solidification t0 of the mixture. Therefore, the composition can advantageously avoid using metal salts in rubber mixtures, without reducing other performance qualities (such as durability and molding). The proposed solution can comprehensively improve the impact on the environment, and reduce the cost of the mixture.

[0144] Preparation of composition

[0145] The composition used in the context of the present invention is manufactured using two successive preparation stages known to those skilled in the art in a suitable mixer:

[0146] - a first stage of thermomechanical processing or kneading ("non-productive" stage), which can be carried out in a single thermomechanical step, during which all the necessary components, in particular the elastomeric matrix, the fillers and, in addition to the crosslinking system, the various other optional additives, are introduced into a suitable mixer, for example a standard internal mixer (for example of the 'Banbury' type). During the thermomechanical kneading, the filler can be added to the elastomer all at once or in batches. In the case where the filler has been added in whole or in part to the elastomer in the form of a masterbatch (as described, for example, in applications WO 97 / 36724 or WO 99 / 16600), what is added is the masterbatch directly kneaded, the other elastomers or fillers not present in the composition in the form of a masterbatch, where appropriate, and the various other optional additives in addition to the crosslinking system.

[0147] The non-productive phase is carried out at high temperature, with a maximum temperature between 130°C and 170°C, and the duration is usually between 2 minutes and 10 minutes.

[0148] - A second stage of mechanical processing ("productive" stage) is carried out in an open mixer (e.g., an open mill), after cooling the mixture obtained during the non-productive first stage to a relatively low temperature (generally less than 110° C., for example, between 40° C. and 100° C.). The crosslinking system is then added and the combined mixture is mixed for a few minutes, for example, between 1 minute and 30 minutes.

[0149] The final composition thus obtained is then calendered, for example in the form of sheets or plates (in particular for laboratory characterizations), or extruded in the form of a semifinished rubber product (or shaped element) that can be used, for example, as an inner layer of a tire.

[0150] The composition may be in an uncured state (before crosslinking or vulcanization) or a cured state (after crosslinking or vulcanization), or may be a semi-finished product that can be used in a tire.

[0151] The crosslinking of the composition can be carried out in a manner known to the person skilled in the art, for example at a temperature between 130° C. and 200° C., preferably under pressure, for a sufficient time which can vary, for example, between 5 minutes and 90 minutes.

[0152] tire

[0153] The above composition is particularly intended for forming the inner wall of a tire having a radial carcass reinforcement, more particularly for being arranged between the reinforcing elements of the carcass reinforcement and the tire cavity, even more particularly between the reinforcing elements of the carcass reinforcement and the inner liner of the tire.

[0154] In certain embodiments, the above-mentioned tire of the present invention is characterized in that the rubber mixture between the reinforcing element of the tire cavity and the carcass reinforcement is composed of at least two rubber mixture layers, and the rubber mixture layer radially adjacent to the radially innermost rubber mixture layer comprises the above-mentioned composition or is composed of the above-mentioned composition. In other words, the rubber mixture layer comprising the above-mentioned composition or being composed of the above-mentioned composition is located between the airtight layer (radially innermost rubber mixture layer) of the carcass reinforcement and the tire. Therefore, the target tire of the present invention is such a tire, in addition to the carcass reinforcement and the airtight layer, the tire also includes an additional layer of rubber mixture as described above. Therefore, this layer is not directly in contact with air. BRIEF DESCRIPTION OF THE DRAWINGS

[0155] The tire of the present invention can be described with reference to the following drawings.

[0156] - Figure 1a is a meridian view of a schematic diagram of a tire according to one embodiment of the invention,

[0157] - Figure 1b yes Figure 1a A partial enlarged view of a portion of the schematic diagram.

[0158] To facilitate understanding, the drawings are not shown to scale. DETAILED DESCRIPTION

[0159] exist Figure 1a and Figure 1b In the embodiment of the present invention, a tire 1 having a size of 315 / 70R 22.5 comprises a radial carcass reinforcement 2 anchored in two beads 3 around bead wires 4. The carcass reinforcement 2 is formed by a single layer of metal cords 11 and two calendering layers 13. The carcass reinforcement 2 is hooped by a crown reinforcement 5, which itself is covered by a tread 6.

[0160] Figure 1b Shows Figure 1a 1 and shows in particular the thickness E of the rubber mix between the inner surface 10 of the cavity 8 of the tire and the point 12 of the reinforcing element 11 closest to said surface 10. This thickness E is equal to the length of the orthogonal projection of the point 12 of the reinforcing element 11 closest to said surface 10 on the surface 10. This thickness E is the sum of the thicknesses of the various rubber mixes situated between said reinforcing elements 11 of the carcass reinforcement 2; it corresponds, on the one hand, to the thickness of the calendered layer 13 situated radially on the inside of the carcass reinforcement and, on the other hand, to the thicknesses e1, e2 of the various layers of rubber mix 14, 15 forming the inner wall of the tire 1. These thicknesses e1, e2 are also equal to the length of the orthogonal projection of a point on one surface of the various layers 14 or 15 under consideration on the other surface.

[0161] The above-mentioned composition is particularly used to form the rubber mixture layer 14 (the rubber mixture layer radially adjacent to the radially innermost rubber mixture layer 15).

[0162] The following examples are given as examples. In no case should they be considered to limit the present invention.

[0163] Example

[0164] Example 1

[0165] Measurement method

[0166] Rheology:

[0167] The measurement is carried out according to standard DIN 53529-Part 3 (June 1983) using an oscillating chamber rheometer at 140° C. The change in rheological torque over time describes the change in the stiffness of the composition caused by the vulcanization reaction. The measurement is carried out according to standard DIN 53529-Part 2 (March 1983).

[0168] t0 is the induction period, which is the time required for the sulfurization reaction to begin.

[0169] tα is the time required to reach a conversion of α%, ie, α% of the difference between the minimum torque and the maximum torque of the crosslinked composition.

[0170] Therefore, t99 is the time required to reach 99% conversion.

[0171] Dynamic properties:

[0172] The dynamic properties, in particular G*10% return at 60°C and G"10% return at 60°C (which represent stiffness and hysteresis, respectively), are measured on a viscoanalyzer (Metravib VA4000) according to standard ASTM D 5992-96. The data are recorded for a sample of the vulcanized composition (with a thickness of 4 mm and a cross section of 400 mm) subjected to a simple alternating sinusoidal shear stress at a frequency of 10 Hz at a temperature of 60°C. 2 The response of a cylindrical specimen.

[0173] For the measurements of the complex dynamic shear modulus (G*) and loss factor (G"), strain amplitude sweeps were performed from 0.1% to 100% peak-to-peak (outward cycle) and then from 100% to 0.1% peak-to-peak (return cycle). For the return cycle, the observed values ​​of G"10% and the value of the G* modulus at 10% strain (expressed as G*10%) are shown.

[0174] Results are expressed relative to the control, which was assigned a value of 100.

[0175] Measurement of reactivity with oxygen:

[0176] The time corresponding to t99 for curing 7 samples of the mixture with a thickness of 6 / 10 mm at 140°C.

[0177] The amount of oxygen initially contained in the sample was measured.

[0178] The remaining 6 samples were placed in an air oven at 85°C for the following aging times: 3 days, 5 days, 7 days, 10 days, 12 days and 14 days.

[0179] The oxygen content contained in each of the six aged samples was then measured.

[0180] For each of the 7 samples, a fixed oxygen content was calculated: oxygen content measured in the aged sample - oxygen content measured in the initial sample.

[0181] The reactivity of the mixture with oxygen then corresponds to the slope of the straight line linking a fixed oxygen content (in % by mass) to the number of days of aging in air at 85° C. (in days).

[0182] Results are expressed relative to the control, which was assigned a value of 100.

[0183] Measurement of oxygen content:

[0184] The solidified mixture is introduced into a pyrolysis chamber at a temperature of about 1000° C., purged by a constant flow of helium.

[0185] The pyrolysate passes through a carbon reducing agent. Oxygen is converted to carbon monoxide. The gas passes through sodium hydroxide and a desiccant to remove acid vapors. Carbon monoxide is separated from other pyrolysis gases by a chromatographic column and detected by a thermal conductivity gas analyzer.

[0186] The oxygen content in the solidified mixture was calculated by using a calibration curve generated with cholesterol. It is expressed as % by mass of the mixture.

[0187] Measurement of oxygen permeability:

[0188] Oxygen permeability values ​​were measured at 60°C using a Mocon Oxtran permeability "tester". A cured sample in the form of a disc with a determined thickness (approximately 0.8 mm to 1 mm) was mounted on the device and made airtight using vacuum grease. One side of the disc was kept at 10 psi of nitrogen, while the other side was kept at 10 psi of oxygen (1 psi = 6894.76 Pa). The increase in oxygen concentration was monitored using a "Coulox" oxygen detector on the face kept under nitrogen. The concentration of oxygen on the face kept under nitrogen (which was able to reach a constant value) was recorded for determining oxygen permeability.

[0189] An arbitrary value of 100 was given to the oxygen permeability of the control, a result less than 100 indicating a decrease in oxygen permeability and therefore a better impermeability.

[0190] Preparation of composition

[0191] The composition is manufactured in a suitable mixer using two consecutive preparation stages known to those skilled in the art: a first stage of thermomechanical processing or kneading at high temperature (sometimes called the "non-productive" stage), the maximum temperature of which is between 110° C. and 200° C., preferably between 130° C. and 180° C., followed by a second stage of mechanical processing at low temperature (generally below 110° C., for example between 60° C. and 100° C.) (sometimes called the "productive" stage), during which the crosslinking system or vulcanization system is conventionally added.

[0192] Curing was carried out at 140°C for a time corresponding to t99.

[0193] The mixtures prepared are as described in Table 1 (components and amounts - amounts are expressed in phr unless otherwise stated).

[0194]

[0195] Table 1: Prepared mixtures

[0196] Mixture ML1 was the control mixture.

[0197] The mixture ML2 is a mixture having the same stiffness as the mixture ML1.

[0198] The mixture ML4 is a mixture having the same stiffness as the mixture ML3.

[0199] result:

[0200] Table 2 shows the properties of the mixture.

[0201]

[0202] Table 2: Properties of the mixture

[0203] Surprisingly, the inventors have found that the use of pyrolytic carbon black in rubber mixtures makes it possible to improve the reactivity of said mixtures with oxygen and the oxygen impermeability without reducing the level of stiffness, while increasing the cure t0 of the mixtures.

[0204] Example 2

[0205] Measurement method

[0206] Measurement of reactivity with oxygen and measurement of oxygen content

[0207] The measurements were performed as described in Example 1.

[0208] Rheology:

[0209] The measurements were performed as described in Example 1.

[0210] Tensile test:

[0211] The tests were carried out according to French standard NF T 46-002 of September 1988. All tensile measurements were carried out according to French standard NF T 40-101 (December 1979) at temperature (100 + / - 2°C) and humidity (50 + / - 5% relative humidity).

[0212] The elongation at break (EB in %) is measured at 100° C. + / - 2° C. on samples cured at 140° C. for 50 minutes, according to standard NF T 46-002.

[0213] The above tests were carried out on the one hand in the initial state and on the other hand after 14 days of accelerated thermo-oxidative ageing, the test composition samples being then placed in a ventilated oven maintained at a temperature of 77° C. and an ambient humidity of 40%.

[0214] Preparation of composition

[0215] The composition is manufactured in a suitable mixer using two consecutive preparation stages known to those skilled in the art: a first stage of thermomechanical processing or kneading at high temperature (sometimes called the "non-productive" stage), the maximum temperature of which is between 110° C. and 200° C., preferably between 130° C. and 180° C., followed by a second stage of mechanical processing at low temperature (generally below 110° C., for example between 60° C. and 100° C.) (sometimes called the "productive" stage), during which the crosslinking system or vulcanization system is conventionally added.

[0216] Curing of mixtures 1 to 5 was carried out at 140° C. for 50 minutes.

[0217] The mixtures prepared are as described in Table 3 (components and amounts - amounts are expressed in phr unless otherwise stated).

[0218]

[0219] Table 3: The prepared mixtures were prepared by adding one or more antioxidants to the components listed above in the following proportions (Table 4). Chemical agent:

[0220]

[0221] Table 4: Nature and content of antioxidants in the mixture

[0222] Mixture ML1 was the control mixture.

[0223] Mixtures ML3, ML4, ML5 are mixtures according to the invention.

[0224] result:

[0225] Table 5 shows the properties of the mixture.

[0226]

[0227] Table 5: Properties of the mixture

[0228] It can be observed that mixtures ML3, ML4 and ML5, containing a total content of antioxidants greater than the usual content (ML1 and ML2), have a better resistance to thermooxidative degradation than mixture ML2, without reducing its ability to react with oxygen and without reducing the curing t0 of the mixture.

[0229] Example 3

[0230] Measurement method

[0231] Measurement of reactivity with oxygen and measurement of oxygen content

[0232] The measurements were performed as described in Example 1.

[0233] Rheology:

[0234] The measurements were performed as described in Example 1.

[0235] Preparation of composition

[0236] The composition is manufactured in a suitable mixer using two consecutive preparation stages known to those skilled in the art: a first stage of thermomechanical processing or kneading at high temperature (sometimes called the "non-productive" stage), the maximum temperature of which is between 110° C. and 200° C., preferably between 130° C. and 180° C., followed by a second stage of mechanical processing at low temperature (generally below 110° C., for example between 60° C. and 100° C.) (sometimes called the "productive" stage), during which the crosslinking system or vulcanization system is conventionally added.

[0237] Curing was carried out at 140°C for 50 minutes.

[0238] Example

[0239] The mixtures prepared are as described in Table 6 (components and amounts - amounts are expressed in phr unless otherwise stated).

[0240]

[0241] Table 6: Prepared mixtures

[0242] Mixtures ML1 and ML6 were control mixtures.

[0243] Mixtures ML3, ML4 and ML5 are mixtures according to the invention.

[0244] Mixtures ML7, ML8 and ML9 are counterexamples without pyrolytic carbon black. They illustrate the effect of different levels of pro-oxidant metal salts (compared to ML6).

[0245] result:

[0246] Table 7 shows the properties of the mixture.

[0247]

[0248] Table 7: Properties of the mixture

[0249] It can be observed that the use of pyrolytic carbon black in rubber compounds makes it possible to reduce the content of metal salts without reducing the reactivity with oxygen, while increasing the cure t0 of the mixture.

Claims

1. A tire having a radial carcass reinforcement consisting of at least one layer of reinforcing elements, comprising a crown reinforcement which is itself radially covered by a tread connected to two beads by two sidewalls, characterized in that The tire comprises, between the reinforcing elements of the carcass reinforcement and the tire cavity, a rubber mixture comprising a composition based on: - isoprene elastomer; - 40 to 70 phr of reinforcing filler, said reinforcing filler comprising at least 10 phr of pyrolytic carbon black, preferably at least 30 phr of pyrolytic carbon black; and - Cross-linking system.

2. Tire according to the preceding claim, wherein: The isoprene elastomer is selected from the group consisting of natural rubber (NR), synthetic polyisoprene (IR), isoprene copolymers (such as copolymers of isobutylene and isoprene), and mixtures thereof.

3. The tire according to claim 1 or 2, wherein: The elastomer is composed of 70 to 100 phr of natural rubber and 0 to 30 phr of synthetic polyisoprene.

4. A tyre according to any one of the preceding claims, wherein: The ash content of the pyrolytic carbon black is in the range of 5 to 30 wt %, preferably in the range of 8 to 25 wt %, more preferably in the range of 10 to 22 wt %, relative to the total weight of the pyrolytic carbon black.

5. A tyre according to any one of the preceding claims, wherein: The sulfur content of the pyrolytic carbon black is greater than 2 wt %, preferably in the range of 2.5 wt % to 5 wt %, relative to the total weight of the pyrolytic carbon black.

6. A tyre according to any one of the preceding claims, wherein: The zinc content of the pyrolytic carbon black is greater than or equal to 2 wt %, preferably in the range of 2.5 wt % to 8 wt %, relative to the total weight of the pyrolytic carbon black.

7. A tyre according to any one of the preceding claims, wherein: The crosslinking system is a vulcanization system based on molecular sulfur and / or a sulfur-donating agent.

8. The tire according to claim 7, wherein: The vulcanization system comprises between 0.5 and 12 phr of sulphur, preferably between 2 and 9 phr.

9. The tire according to claim 7 or 8, wherein: The vulcanization system comprises between 0.1 and 10 phr, preferably between 0.3 and 1.0 phr, of one or more vulcanization accelerators.

10. A tyre according to claim 7, 8 or 9, wherein: The vulcanization system comprises between 1 and 10 phr, preferably between 3.3 and 10 phr, of one or more vulcanization activators.

11. The tire according to any one of the preceding claims, wherein: The composition further comprises one or more agents selected from plasticizers, non-reinforcing fillers, pigments, primary adhesion promoters, pro-oxidant metal salts, protective agents, anti-fatigue agents and reinforcing resins, the protective agent being, for example, anti-ozonant waxes, chemical anti-ozonants, antioxidants.

12. A tyre according to any one of the preceding claims, wherein: The composition also comprises 0.3% to 4% by mass of one or more antioxidants relative to the total mass of the composition.

13. A tyre according to any one of the preceding claims, wherein: The composition also comprises one or more pro-oxidant metal salts, the pro-oxidant metal salts being determined on a metal basis in an amount varying from 0.05 g of metal to 0.15 g of metal per 100 g of the composition.

14. A tyre according to any one of the preceding claims, wherein: The rubber mix between the reinforcing elements of the carcass reinforcement and the tire cavity consists of at least two rubber mix layers, the rubber mix layer radially adjacent to the radially innermost rubber mix layer comprising a composition as claimed in any one of claims 1 to 13.

Citation Information

Patent Citations

  • Reinforcing aluminum-based filler and rubber composition comprising such a filter

    US6610261B1

  • Rubber composition for a tire, based on diene elastomer and a reinforcing titanium oxide

    US6747087B2

  • Organosilicon compounds

    US6849754B2

  • Novel elastomer composites, method and apparatus

    WO1997036724A2

  • Blocked mercaptosilane coupling agents for filled rubbers

    WO1999009036A1